QOL-41. CARDIAC DYSFUNCTION IN MEDULLOBLASTOMA SURVIVORS TREATED WITH PHOTON IRRADIATION. (4th December 2020) - Cacciotti, Chantel; Chordas, Christine; Valentino, Kate; Allen, Rudy; Manley, Peter; Pillay-Smiley, Natasha
Abstract: BACKGROUND: Medulloblastoma is an aggressive central nervous system (CNS) tumor that occurs mostly in the pediatric population. Treatment includes surgical resection, craniospinal radiation (CSI) and chemotherapy. Children who receive standard photon radiation (RT) are at risk for cardiac toxicities. Potential late effects include coronary artery disease, left ventricular scarring and dysfunction, valvular damage and atherosclerosis. Current survivorship guidelines recommend routine ECHO surveillance for these patients but this comes at significant health care costs over a lifetime. We describe the experience of cardiac dysfunction in medulloblastoma survivors in a multi-institution study. METHODS: A retrospective chart review of medulloblastoma patients treated between 1980 and 2010 with radiation at Lurie Children's Hospital and Dana-Farber/ Boston Children's Hospital who had an echocardiogram done following completion of therapy. RESULTS: 168 patients were treated for medulloblastoma during the study time. Of whom, 80 patients had echocardiogram follow up and 76 received photon irradiation. The latter were included in the study. The mean age at CSI was 8.6 years (range 2.9- 20), and mean number of years post RT at echocardiogram 7.4 years (range 2–16). Mean ejection fraction (EF) was 60.03% and shortening fraction (SF) 33.8%. Four patients (5%) had abnormal results, all of which had EF<50%. CONCLUSION: Patients who received craniospinal irradiation for medulloblastoma therapy have relatively normal echocardiograms post treatment. Although RT may result in cardiac risks, echocardiograms may not be the most cost effective or efficacious mode to evaluate the risk in these survivors long term.